Methicillin-Resistant Staphylococcus aureus USA300 Clone in Long-Term Care Facility - Tattevin, Pierre (Centers for Disease Control and Prevention, 2009)
We performed a longitudinal analysis of 661 methicillin-resistant Staphylococcus aureus (MRSA) isolates obtained from patients in a long-term care facility. USA300 clone increased from 11.3% of all MRSA isolates in 2002 to 64.0% in 2006 (p<0.0001) and was mostly recovered from skin or skin structures (64.3% vs. 27.0% for non-USA300 MRSA; p<0.0001).